Os fatores determinantes da ado????o da inova????o verde para o desempenho organizacional no agroneg??cio - Silva, Alexandre Rodrigues da (2019)
In this research, we developed two studies in order to answer the following research question: what are the determinants of the adoption of green innovation for organizational performance in agribusiness? The main objective of this work was to identify the determinants of green innovation adoption for organizational performance in agribusiness. Study I presented a bibliometric study of citation, cocitation and pairing in which we sought to understand the intellectual and mainstream structure of innovation research, providing a theoretical basis for continuing the study. The results of study I pointed out a relationship between performance and adoption of innovation where the determining factors lead to adoption, providing greater gains and better productivity. Study II contributed to the analysis of the adoption of green innovation (biodigestor), responding the research question. It is a qualitative study (semi-structured interview) in the agribusiness production chain (manioc, swine - a case - and poultry - a case) to identify the determinants of green innovation in organizational performance. Study II demonstrated positive results in green innovation adoption (biodigestor), through the determining factors, for organizational performance in agribusiness. Our studies have contributed to clarify existing theories and empirical research on green innovation adoption in a specific context. It also demonstrates the determinants that lead companies to adopt a particular innovation by providing an agenda for managers regarding the positive aspects of innovation adoption in agribusiness. In conclusion, we pointed out that the main determining factor was the economic benefit provided by the biodigester, which is a waste treatment method that delivers environmental benefits, as long as it is correctly and efficiently scaled.